2017
DOI: 10.1530/joe-16-0568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of androgen on Kiss1 expression and luteinizing hormone release in female rats

Abstract: Hyperandrogenic women have various grades of ovulatory dysfunction, which lead to infertility. The purpose of this study was to determine whether chronic exposure to androgen affects the expression of kisspeptin (ovulation and follicle development regulator) or release of luteinizing hormone (LH) in female rats. Weaned females were subcutaneously implanted with 90-day continuous-release pellets of 5α-dihydrotestosterone (DHT) and studied after 10 weeks of age. Number of -expressing cells in both the anterovent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
3
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
1
21
3
2
Order By: Relevance
“…When we used 10 nM DHT ex vivo, levels used by Foecking et al (41,42), we also observed reduced basal LH secretion in control mice. Further, testosterone has been shown to suppress LH and FSH secretion independently of peripheral aromatization in both men (43)(44)(45) and women (9,43). Although LH is often elevated in women with PCOS and in nonrodent animal models of PCOS, this could be due to the timing of androgen exposure, adult vs. gestational androgen exposure, and not the species differences.…”
Section: Discussionmentioning
confidence: 99%
“…When we used 10 nM DHT ex vivo, levels used by Foecking et al (41,42), we also observed reduced basal LH secretion in control mice. Further, testosterone has been shown to suppress LH and FSH secretion independently of peripheral aromatization in both men (43)(44)(45) and women (9,43). Although LH is often elevated in women with PCOS and in nonrodent animal models of PCOS, this could be due to the timing of androgen exposure, adult vs. gestational androgen exposure, and not the species differences.…”
Section: Discussionmentioning
confidence: 99%
“…In this highly coordinated system, both E 2 and T act as feedback signals. GnRH neurons lack estrogen receptor α receptors, in contrast to kisspeptin neurons that mediate such feedback [22]. Feedback on LH secretion has been studied in men with central hypogonadism lacking GnRH signaling [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kondo et al [28] who studied ARC kisspeptin immune reactivity by using antiprogestin R4486 found that besides the increase in the LH level, there was also an increase in the number of kisspeptin-positive cells in the hypothalamus. On the contrary, Marcondes et al [29,30] did not agree with this. ey suggested that low kisspeptin expression in testosterone-treated rats might contribute to anovulation and decrease in LH secretion.…”
Section: Discussionmentioning
confidence: 88%
“…Peripheral administration of kisspeptin in adult mice caused a dramatic increase in free testosterone level [6]. On the contrary, Iwata et al [30] found that hyperandrogenism in adult rats caused a decrease in the number of KISS1expressing cells in both AVPV and ARC nucleus. Additionally, they argued that the ARC nucleus (containing estrogen receptor) also has an androgen receptor which can be affected by excess androgen and so cause negative feedback to kisspeptin.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation